The Features of Children’s Cultural Activities in the Mirror of the Changes in Children Culture (Training and Practice : Journal of Educational Sciences, 2015)
Children’s culture is regarded either as material, financial and spiritual values of human culture that can awake children's interest and are made and organized for them, or they are created by children give them pleasure for the day and promote their development. In our research we made a survey with 500 preschool children in order to get to know their favourite toys and stories, their story-listening habits, their practices of using a computer and their future orientation in the frame of the changes in children culture. The results of our research may contribute to understand the world created by children, may help teachers, parents and kindergarten teacher trainers, moreover may develop education in early childhood and kindergarten teacher training, and may lead to institutional innovations as well.